An examination of athletic trainers' occupational recovery experiences during time after work - Gnacinski, S. L.; Nai, M.; Brady, M.; Meyer, B. B.; Newman, N. (Journal of Athletic Training, 2020)
Context: Although researchers have directed scholars toward investigating the effectiveness of the nonwork personal time of athletic trainers (ATs), no one has characterized the occupational recovery experiences of ATs. Objective: To examine the reliability and validity of the Recovery Experience Questionnaire (REQ) for use in AT populations. Design: Cross-sectional study. Setting: Web-based survey. Patients or Other Participants: A total of 144 ATs (71 men, 73 women) working in a variety of National Collegiate Athletic Association sports across all levels of competition. Main Outcome Measure(s): The REQ was administered to assess the AT recovery experience. Results: Preliminary evidence emerged for the reliability (? = 0.80-0.90) and validity of the REQ for use in AT populations. Weak linear relationships were identified between stress and perceptions of psychological detachment (r = -0.314, P < .001), mastery (r = -0.179, P = .32), control (r = -0.284, P = .001), and relaxation (r = -0.157, P = .06). Conclusions: Our results support measuring and applying occupational recovery for AT stress and work-life balance. Given that occupational recovery as a construct was only weakly related to stress, it is clearly a unique and distinct variable worth considering within the work-life balance line of inquiry.